Prevalence of cervical intraepithelial neoplasia grades II/III and cervical cancer in patients with cytological diagnosis of atypical squamous cells when high-grade intraepithelial lesions (ASC-H) cannot be ruled out - Cytryn, Andréa; Russomano, Fábio Bastos; Camargo, Maria José de; Zardo, Lucília Maria Gama; Horta, Nilza Maria Sobral Rebelo; Fonseca, Rachel de Carvalho Silveira de Paula; Tristão, Maria Aparecida; Monteiro, Aparecida Cristina Sampaio (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: The latest update of the Bethesda System divided the category of atypical squamous cells of undetermined significance (ASCUS) into ASC-US (undetermined significance) and ASC-H (high-grade intraepithelial lesion cannot be ruled out). The aims here were to measure the prevalence of pre-invasive lesions (cervical intraepithelial neoplasia, CIN II/III) and cervical cancer among patients referred to Instituto Fernandes Figueira (IFF) with ASC-H cytology, and compare them with ASC-US cases. DESIGN AND SETTING: Cross-sectional study with retrospective data collection, at the IFF Cervical Pathology outpatient clinic. METHODS: ASCUS cases referred to IFF from November 1997 to September 2007 were reviewed according to the 2001 Bethesda System to reach cytological consensus. The resulting ASC-H and ASC-US cases, along with new cases, were analyzed relative to the outcome of interest. The histological diagnosis (or cytocolposcopic follow-up in cases without such diagnosis) was taken as the gold standard. RESULTS: The prevalence of CIN II/III in cases with ASC-H cytology was 19.29% (95% confidence interval, CI, 9.05-29.55%) and the risk of these lesions was greater among patients with ASC-H than with ASC-US cytology (prevalence ratio, PR, 10.42; 95% CI, 2.39-45.47; P = 0.0000764). Pre-invasive lesions were more frequently found in patients under 50 years of age with ASC-H cytology (PR, 2.67; 95% CI, 0.38-18.83); P = 0.2786998). There were no uterine cervical cancer cases. CONCLUSION: The prevalence of CIN II/III in patients with ASC-H cytology was significantly higher than with ASC-US, and division into ASC diagnostic subcategories had good capacity for discriminating the presence of pre-invasive lesions.